Otimização de manobras orbitais para remoção de detritos espaciais - Tsuji, André Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Progress in space and satellite research is of great importance in meteorology, telecommunications, aerial image processing of the Earth and in other diverse fields. Equipment used for such purposes has a certain useful life and, at the end of this period, it is called space waste or debris. The lack of proper care with the disposal of these residues keeps them in orbit close to the planet, thus increasing the risk of accidents with astronauts in service and with artificial satellites that are in operation. This work involves a method of cleaning the Earth's orbit where an impulse will be applied to the debri through a laser cannon located on the Earth's surface. Such an impulse must disturb the target's orbital motion so that its new trajectory is directed into the Earth's atmosphere and undergoes combustion.

O progresso em pesquisas espaciais e de satélites é de grande importância em trabalhos envolvendo meteorologia, telecomunicações, processamento de imagens aéreas da Terra e em outras diversas áreas. Equipamentos usados para tais fins possuem determinado tempo de vida útil e, ao término desse período, estes são chamados de lixos espaciais ou debris. A ausência dos devidos cuidados com o descarte desses resíduos os mantém em órbita nas proximidades do planeta, aumentando assim o risco de acidentes com astronautas em serviço e com satélites artificiais que estão em operação. Este trabalho aborda um método de limpeza da órbita terrestre onde será aplicado um impulso no debri através de um canhão de laser localizado na superfície terrestre. Tal impulso deve perturbar o movimento orbital do alvo para que sua nova trajetória seja direcionada para dentro da atmosfera terrestre e sofra combustão.
Optimization of orbital maneuvers for space debris removal
Keywords: Debri; Space junk cleanup; Space junk; Safety in the operation of satellites; Limpeza de lixo espacial; Lixo espacial; Segurança na operação de satélites; Órbitas; Satélites Órbitas; Perturbação (Astronomia)